Numerical evaluation of periodic transverse vibration of elastic connecting rods in a six-link mechanism - Khang, Nguyen Van; Khiem, Vu Van (Vietnam Journal of Mechanics, 1997)
Application of the substructure method and d’Alembert’s principle to deriving the differential equation of motion of a six-link mechanism with two elastic connecting rods is presented. In the case of stationary motion, the generalized Ritz’s method has been applied to obtain system of linear differential equations with periodic coefficients. We have written computer programs to check conditions of dynamic stability and to find periodic solutions of the obtained equations. Numerical examples are given and from which the effect of elastic factors on articulation reactions is evaluated.